The Role Of Foreign Ownership: The Influence Of Accounting Conservatism And Corporate Social Responsibility Disclosure - Simanjuntak, Gracesiela Yosephine; Sagala, Farida; Sagala, Lamria; Situmorang, Duma Rahel; Panjaitan, Rike Yolanda (Program Studi Akuntansi Universitas Simalungun, 2024)
This literature study has explored the influence of accounting conservatism and disclosure of corporate social responsibility. This paper wants to analyze how the role of foreign ownership can strengthen or weaken the influence of accounting conservatism and corporate social responsibility disclosure. Using a sample of 225 out of 810 companies listed on the Indonesia Stock Exchange for the 2019 - 2023 period. Researchers found that companies with higher CSR disclosures tend to have more conservative financial reporting practices. However, researchers observed that foreign ownership was able to weaken the influence (negative moderation) of accounting conservatism and CSR disclosure, in line with agency theory. Researchers also found that foreign ownership and the level of institutional ownership have a significant negative influence on accounting conservatism and CSR disclosure. Meanwhile, managerial ownership does not have a significant influence on accounting conservatism and CSR disclosure. Researchers found that foreign ownership, institutional ownership and managerial ownership simultaneously had a negative and significant effect on accounting conservatism and CSR disclosure